2013
DOI: 10.1080/07481187.2012.673533
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death and the Quest for Meaning After the Loss of a Child

Abstract: This study examined patterns of making meaning among 155 parents whose children died from a variety of violent and non-violent causes. Findings indicated 53% of violent loss survivors could not make sense of their loss, as compared to 32% of non-violent loss survivors. Overall, there was overlap in sense-making strategies across different causes of death, with many parents invoking spiritual and religious meanings and the cultivation of empathy for the suffering of others. Nonetheless, violent loss survivors d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 51 publications
(84 reference statements)
4
73
0
5
Order By: Relevance
“…For example, previous studies have suggested that risk factors for PGD, including that of violent loss, increase symptoms of PGD by hindering meaning making such that the bereft are unable to ‘make sense’ of the death or its aftermath (Milman, Neimeyer, Fitzpatrick, MacKinnon, Muis, & Cohen, under review; Currier, Holland, Coleman, & Neimeyer, 2007; Lichtenthal, Neimeyer, Currier, Roberts, & Jordan, 2013; Neimeyer, Baldwin, & Gillies, 2006; Rozalski, Holland, & Neimeyer, 2017). Building on this research, this study examines which themes of meaning are disrupted specifically following violent loss with the aim of informing preventive interventions that facilitate meaning making in a manner that mitigates symptoms of PGD among the violently bereft.…”
mentioning
confidence: 99%
“…For example, previous studies have suggested that risk factors for PGD, including that of violent loss, increase symptoms of PGD by hindering meaning making such that the bereft are unable to ‘make sense’ of the death or its aftermath (Milman, Neimeyer, Fitzpatrick, MacKinnon, Muis, & Cohen, under review; Currier, Holland, Coleman, & Neimeyer, 2007; Lichtenthal, Neimeyer, Currier, Roberts, & Jordan, 2013; Neimeyer, Baldwin, & Gillies, 2006; Rozalski, Holland, & Neimeyer, 2017). Building on this research, this study examines which themes of meaning are disrupted specifically following violent loss with the aim of informing preventive interventions that facilitate meaning making in a manner that mitigates symptoms of PGD among the violently bereft.…”
mentioning
confidence: 99%
“…The relationship between PTG and type of child's death after birth was not analysed, because of the small number of subjects. Available data (Lichtenthal, Neimeyer, Currier, Roberts, & Jordan, 2013) indicate that bereaved parents whose children died of illness report higher levels of PTG than those whose children died of injury (i.e. accident, suicide, and homicide).…”
Section: Discussionmentioning
confidence: 99%
“…Those who significantly struggle with maintaining a sense of meaning in life or purpose and/or making sense of the death may be at increased risk for mental and physical health problems (Lichtenthal et al, 2010; Neimeyer & Sands, 2011; Lichtenthal et al, 2013). …”
Section: Risk Factorsmentioning
confidence: 99%